Non-English Major Students’ Interest on Applying Speaking In Daily Life - Anggi Ariani Br. Sitepu; Aisyah Hadi; Desi Lestari; Ismarani Fikri Arifah; Surya Ramadhan; Wandi Syahfutra; Novela Nurafrezah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
This study aims to investigate the factors influencing non-English major students' interest in applying their english speaking skills in daily life. The research focuses on Chemical Engineering students of the University of Muhammadiyah Riau, Class of 2024. Utilizing a quantitative approach, data were collected through a structured questionnaire using a 5-point Likert scale, which measured students' interest in speaking English outside the classroom. A sample of 45 students was selected through random sampling from a population of 51, with results showing that 81% of respondents expressed an interest in using English in their daily interactions. The study identifies key factors affecting students' speaking interest, including self-confidence, social environment, and motivation. Results suggest that a supportive environment and intrinsic and extrinsic motivations significantly influence students' willingness to speak English. However, challenges such as lack of confidence and fear of making mistakes remain significant barriers. The study highlights the need for targeted interventions to foster practical English use and bridge the gap between academic learning and real-world communication. These findings contribute to the development of more effective strategies for encouraging non-English major students to apply their English skills in everyday life.